**preview**has

**blurred**sections. Sign up to view the full version! View Full Document

**Unformatted text preview: **When using the product rule, if the bases are the same then one would keep the base and add the
exponents together.
EXAMPLE: 63x64 = 63+4 = 67
When raising a product to a power, one needs to raise each factor to the power of exponents.
EXAMPLE: (xy)3 = x3y3
The negative exponents rule is difficult for me to explain, but as I understand it, one takes the reciprocal
of the base.
EXAMPLE: 4-2 = 1
42
1 = 42
or
4-2
Expression using scientific notation:
1
1010
answer: 1 x 10-10 or 0.0000000001
...

View Full Document